Einsatzgrenzenerweiterung und Flexibilitätssteigerung von einseitig wirkenden mechanischen Fügeverfahren durch prozessintegrierte Fügeteilerwärmung für den stahlintensiven Leichtbau - Ivanjko, Martin; Meschut, Gerson (9. Fügetechnisches Gemeinschaftskolloquium)

Entwicklung und Qualifizierung des Fließlochformschraubens zum Fügen höchstfester Stahlbleche und -profile - Ivanjko, Martin; Meschut, Gerson (9. Fügetechnisches Gemeinschaftskolloquium)

Gibt es einen Einstellungswandel der Studierenden in Bezug auf das Forschende Lernen im Praxissemester? – Ein Kohortenvergleich - Bloh, Bea

Economic Retirement Age and Lifelong Learning - a theoretical model with heterogeneous labor and biased technical change - Gries, Thomas; Jungblut, Stefan; Krieger, Tim; Meyer, Henning (German Economic Review)

Systematik zur Gestaltung der Wertschöpfung für digitalisierte hybride Marktleistungen - Mittag, Tobias

Vorausschau und Technologieplanung. 15. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 21. und 22. November 2019 - Gausemeier, Jürgen

Systematik zur Ableitung bedarfsgerechter Systems Engineering Leitfäden im Maschinenbau - Schierbaum, Anja Maria

Forschendes Lernen in Praxissemester und Beruf – Einstellungen und Handlungsintention von Lehramtsstudierenden - Homt, Martina; van Ophuysen, Stefanie (Beiträge zur Lehrerinnen- und Lehrerbildung)

Die Vorstellungen Lehramtsstudierender von Forschendem Lernen im Verlauf des Praxissemesters - Homt, Martina; van Ophuysen, Stefanie

Forschend Lernen in Praxissemester und LehrerInnenberuf – Einstellungen und Handlungsintention von Lehramtsstudierenden - Homt, Martina; van Ophuysen, Stefanie

Die Nutzenerwartung gegenüber Forschendem Lernen in Praxissemester und Beruf – Einstellungsveränderungen Lehramtsstudierender im Verlauf des Praxissemesters - Homt, Martina

Orientierungs(un)willig? – Zu studienbereichsspezifischen Unterschieden in der Intention zur beruflichen Orientierung - Wehde, Janis; Schäfer, Laura; Schlegel, Anina; Oster, Leonie; Beeck, Valentina

Lernen von Praxiskompetenz - Bloh, Thiemo

Digitalisierung in der Lehrerbildung. Herausforderungen, Entwicklungsfelder und Förderung von Gesamtkonzepten - Ackeren, Isabell van; Aufenanger, Stefan; Eickelmann, Birgit; Friedrich, Steffen; Kammerl, Rudolf; Knopf, Julia; Mayrberger, Kerstin; Scheika, Heike; Scheiter, Katharina; Schiefner-Rohs, Mandy (Die Deutsche Schule)
Auf Einladung des Bundesministeriums für Bildung und Forschung (BMBF) hat sich im Sommer 2018 eine bundesweite Expertengruppe mit zentralen Herausforderungen im Bereich der Digitalisierung in der Lehrerbildung beschäftigt. Auf der Grundlage der Einschätzung von Expert*innen sowie weiterer wissenschaftlicher Befunde und Erkenntnisse wurde vor diesem Hintergrund - auch unter Berücksichtigung der finanziellen Rahmenbedingungen - ein Konzept entworfen, wie eine entsprechende Förderlinie im Rahmen der Qualitätsoffensive Lehrerbildung aussehen könnte. Auch wurde beraten, welche Anforderungen an die Anträge im Sinne zukunftsweisender Gesamtkonzepte zu stellen sind. Der Beitrag stellt insofern ein vertiefendes Hintergrundpapier zur Förderrichtlinie des BMBF in der Qualitätsoffensive Lehrerbildung mit dem Schwerpunkt Digitalisierung dar und eröffnet gleichzeitig Perspektiven für zukünftige Entwicklungen. (DIPF/Orig.)

Unerwartet erfolgreiche Schulen im digitalen Zeitalter. Eine Analyse von Schulmerkmalen resilienter Schultypen auf Grundlage der IEA-Studie ICILS 2013 - Eickelmann, Birgit; Gerick, Julia; Vennemann, Mario (Journal for Educational Research Online (JERO))
Die fortschreitende Digitalisierung stellt Schulen bei der Vermittlung von computer- und informationsbezogenen Kompetenzen vor neue Herausforderungen. In diesem Zusammenhang konnte die International Computer and Information Literacy Study (ICILS) 2013 zeigen, dass die Achtklässlerinnen und Achtklässler in Deutschland im internationalen Vergleich lediglich über durchschnittliche computer- und informationsbezogene Kompetenzen verfügen. Zudem konnten substantielle soziale Disparitäten hinsichtlich eines kompetenten Umgangs mit neuen Technologien festgestellt werden. Ausgehend von der Beobachtung, dass sich einerseits zahlreiche Schulen in besonders heraufordernden Lagen im besonderen Maße für die Unterstützung des Erwerbs digitaler Kompetenzen ihrer Schülerinnen und Schüler engagieren und sich andererseits für andere Domänen wie Lesen und Mathematik auf der Basis empirischer Studien Schulen identifizieren lassen, die trotz herausfordernder sozialer Schülerkomposition ein hohes Kompetenzniveau erreichen, betrachtet der Beitrag unerwartet erfolgreiche Schulen im Bereich der computer- und informationsbezogenen Kompetenzen. Im Fokus steht daher, inwiefern sich diese auch als organisational resilient bezeichneten Schulen aufgrund von Schulmerkmalen zu einer Typologie zusammenfassen lassen und wie sich relevante schulische Merkmale auch unter Berücksichtigung des Schulleitungshandeln innerhalb der vier identifizierbaren Schulgruppen beschreiben lassen. (DIPF/Orig.)

Schule und Lernen unter Bedingungen der Digitalisierung. Wie können Potenziale digitaler Medien für die Entwicklung der Lernkultur in Sekundarschulen genutzt werden? - Eickelmann, Birgit (Pädagogik)

Unterrichtliche Lernaktivitäten mit digitalen Medien in der Sekundarstufe I in Deutschland und Nordrhein-Westfalen - Jarsinski, Sascha; Eickelmann, Birgit; Lorenz, Ramona (SchulVerwaltung NRW)

Schulentwicklungsprozesse mit digitalen Medien – Pädagogisches Leitungshandeln im Kontext der Digitalisierung - Gerick, Julia; Eickelmann, Birgit (Jahrbuch Schulleitung 2019. Befunde und Impulse zu den Handlungsfeldern des Schulmanagements)

Digital Learning Leadership – Konzepte für eine zukunftsweisende Qualifizierung schulischer Führungskräfte - Eickelmann, Birgit; Fugmann, Martin; Neubauer, Daniel (Jahrbuch Schulleitung 2019. Befunde und Impulse zu den Handlungsfeldern des Schulmanagements)

Untersuchung des technischen und pädagogischen Supports an Schulen der Sekundarstufe I in Deutschland – Eine vertiefende Untersuchung zur Studie ‚Schule digital – der Länderindikator 2017‘. Ergebnisbericht der Lehrerbefragung - Bos, Wilfried; Lorenz, Ramona; Endberg, Manuela; Eickelmann, Birgit

Chancen des digitalen Lernens in der Ganztagsschule - Eickelmann, Birgit; Drossel, Kerstin (Jahrbuch Ganztagsschule 2019/20)

Abschlussbericht im Rahmen der wissenschaftlichen Begleitung der Evaluation des Projekts ‚Lernen mit digitalen Medien‘ (Phase II) in Schleswig-Holstein - Gerick, Julia; Eickelmann, Birgit

Herausforderungen und Zielsetzungen im Kontext der Digitalisierung von Schule und Unterricht, Teil 3 - Eickelmann, Birgit; Gerick, Julia (SchulVerwaltung Bayern, Fachzeitschrift für Schulentwicklung und Schulmanagement)

Herausforderungen und Zielsetzungen im Kontext der Digitalisierung von Schule und Unterricht, Teil 2 - Eickelmann, Birgit; Gerick, Julia (SchulVerwaltung Bayern, Fachzeitschrift für Schulentwicklung und Schulmanagement)

Herausforderungen und Zielsetzungen im Kontext der Digitalisierung von Schule und Unterricht, Teil 1 - Eickelmann, Birgit; Gerick, Julia (SchulVerwaltung Bayern, Fachzeitschrift für Schulentwicklung und Schulmanagement)

Spezifika der Digitalisierung im Schulbereich. Merkmale von Schulen, die den digitalen Wandel zukunftsweisend gestalten - Eickelmann, Birgit (SchulVerwaltung NRW, Fachzeitschrift für Schulentwicklung und Schulmanagement)

Implikationen aus dem Projekt ‚Lernen mit digitalen Medien‘ – Entwicklungsperspektiven aus Sicht der Schulforschung und der Projektverantwortlichen der Bildungsadministration - Eickelmann, Birgit; Gerick, Julia; Ramm, Gesa (Praxis des digitalen Lehrens und Lernens. Befunde und Erfahrungen. Schulmanagement-Handbuch)

Wissenschaftliche Begleitung des Projekts ‚Lernen mit digitalen Medien‘ und Evaluationsergebnisse aus Projektphase II - Gerick, Julia; Eickelmann, Birgit; Ramm, Gesa; Akue-Dovi, Jennifer (Praxis des digitalen Lehrens und Lernens. Befunde und Erfahrungen. Schulmanagement-Handbuch)

Das Projekt ‚Lernen mit digitalen Medien‘ - Ramm, Gesa; Gerick, Julia; Eickelmann, Birgit (Praxis des digitalen Lehrens und Lernens. Befunde und Erfahrungen. Schulmanagement-Handbuch)

Praxis des digitalen Lehrens und Lernens. Befunde und Erfahrungen. Schulmanagement-Handbuch

Potenziale der Tabletnutzung im Unterricht zur individuellen Förderung – Analysen und Forschungsperspektiven - Drossel, Kerstin; Eickelmann, Birgit (Individuelle Förderung im Unterricht. Empirische Befunde und Hinweise für die Praxis)

Measuring secondary school students’ competence in computational thinking in ICILS 2018 – challenges, concepts, and potential implications for school systems around the world - Eickelmann, Birgit (Computational Thinking Education)

Core Themes in the Second International Handbook of Information Technology in Primary and Secondary Education: A Bird’s Eye View - Voogt, Joke; Knezek, Geral; Christensen, Rhonda; Tondeur, Jo; Ifenthaler, Dirk; Eickelmann, Birgit (Proceedings of EdMedia + Innovate Learning 2019)

'Digitalisierung meets Schule' - Welchen Stellenwert haben pädagogische Führungskräfte in Zeiten der Digitalisierung? - Fugmann, Martin; Eickelmann, Birgit; Neubauer, Dirk (b:sl. Beruf: Schulleitung. Das Fachmagazin für Schulleitungen in Deutschland)

Möglichkeiten des Transfers schulischer Innovationen im Kontext des Lernens mit digitalen Medien an Grundschulen - Gerick, Julia; Eickelmann, Birgit (Grundschulpädagogik zwischen Wissenschaft und Transfer (Jahrbuch Grundschulforschung))

An Area Efficient 19.25 GHz to 77 GHz Gilbert Cell Frequency Quadrupler with 55% Shrinked Delay Lines in 130nm SiGe BiCMOS - Kruse, Stephan (IEEE MTT-S International Microwave and RF Conference 2019)
This paper presents an area-efficient 19.25 GHz to 77 GHz frequency quadrupler for automotive radar applications. To reduce chip area, the delay lines of each doubler stage have been drastically shrunk by means of meandering, slow wave structures, and capacitive loading. Additional circuit techniques were applied to further reduce chip area. Compared to previously published Gilbert cell frequency multipliers the presented quadrupler achieves the shortest electrical length of the delay lines reported so far allowing for compact, low-cost radar transceivers. The chip was implemented in a IHP 130nm SiGe BiCMOS technology (f T /f max =240/340GHz). It dissipates 91.5mW from a 3.3V supply.

70 GHz Large-signal Bandwidth Sampler Using Current-mode Integrate-and-Hold Circuit in 130 nm SiGe BiCMOS Technology - Wu, Liang; Weizel, Maxim; Scheytt, Christoph (Asia-Pacific Microwave Conference (APMC))
This paper presents a broadband sampler IC using a current-mode integrated-and-hold-circuit (IHC) as sampling circuit. The sampler IC exhibits 1dB large-signal bandwidth of 70 GHz and excellent signal integrity on hold-mode. With a sampling rate of 5 GS/s, it achieves effective number of bits (ENOB) of 6 bit at 9.9 GHz input frequency. The chip was fabricated in a 130 nm SiGe BiCMOS technology from IHP.

A 70 GHz Small-signal Bandwidth 40 GS/s Track-and-Hold Amplifier in 130 nm SiGe BiCMOS Technology - Wu, Liang; Weizel, Maxim; Scheytt, Christoph (26th IEEE International Conference on Electronics Circuits and Systems (ICECS))
This paper presents a broadband track-and-hold amplifier (THA) based on switched-emitter-follower (SEF) topology. The THA exhibits a record 3dB small-signal bandwidth of 70 GHz. With the high sampling rate of 40 GS/s, it achieves an effective number of bits (ENOB) of 7.5 bit at 1 GHz input frequency and an ENOB of >5 bit up to 15 GHz input frequency. The chip was fabricated in a 130 nm SiGe BiCMOS technology from IHP (SG13G2). It draws 110 mA from a -4 V supply voltage, dissipating 440 mW.

An overview of the Meteracom Project - Humphreys, David; Berekovic, Mladen; Kallfass, Ingmar; Scheytt, Christoph; Kuerner, Thomas; Jukan, Admela; Schneider, Thomas; Kleine-Ostmann, Thomas; Koch, Martin; Thomae, Reiner (Proc. 43-nd Meeting of the Wireless World Research Forum (WWRF)",)
We overview the 3-year Meteracom project which will provide traceability to the SI for THz communication measurement parameters. The key objectives are to develop new metrological methods to characterize the measurement systems, system components and propagation channels. The final objective is to develop metrology for functionality and signal integrity of THz communication systems; particularly device discovery and beam tracking, determination of physical layer parameters for digital transmission and real-time performance evaluation.

A 5.8 GHz CMOS Analog Front-End Targeting RF Energy Harvesting for Microwave RFIDs with MIMO Reader - Haddadian, Sanaz; Scheytt, Christoph (IEEE International Conference on RFID Technology & Application (RFID-TA))
Targeting the feasible application of microwave RFID systems with MIMO reader technology for tracking small objects in multipath fading conditions, we present a fully integrated Analog Front-End (AFE) designed and fabricated in a standard 65-nm CMOS technology for low power passive RFID tags in the 5.8 GHz ISM band. A differential drive power scavenging unit is dimensioned to provide a 1.2 V rectified voltage resulting in a 1 V regulated voltage for the AFE while supplying a 50 μW load. Transistors with standard threshold voltage (V th ) have been used for implementation. Measurements of the fabricated circuits show a maximum Power Conversion Efficiency (PCE) of 71.8% at -12.5 dBm, and an input quality factor (Q-factor) of approximately 10.

RISC-V Extensions for Bit Manipulation Instructions - Koppelmann, Bastian; Adelt, Peer; Müller, Wolfgang; Scheytt, Christoph (29th International Symposium on Power and Timing Modeling, Optimization and Simulation (PATMOS))
Embedded systems require a high energy efficiency in combination with an optimized performance. As such, Bit Manipulation Instructions (BMIs) were introduced for x86 and ARMv8 to improve the runtime efficiency and power dissipation of the compiled software for various applications. Though the RISC-V platform is meanwhile widely accepted for embedded systems application, its instruction set architecture (ISA) currently still supports only two basic BMIs.We introduce ten advanced BMIs for the RISC-V ISA and implemented them on Berkeley's Rocket CPU [1], which we synthesized for the Artix-7 FPGA and the TSMC 65nm cell library. Our RISC-V BMI definitions are based on an analysis and combination of existing x86 and ARMv8 BMIs. Our Rocket CPU hardware extensions show that RISC-V BMI extensions have no negative impact on the critical path of the execution pipeline. Our software evaluations show that we can, for example, expect a significant impact for time and power consuming cryptographic applications.

An IEEE 802.11 Compliant SDR-Based System for Vehicular Visible Light Communications - Amjad, Muhammad Sohaib; Tebruegge, Claas; Memedi, Agon; Kruse, Stephan; Kress, Christian; Scheytt, Christoph; Dressler, Falko (IEEE International Conference on Communications (ICC))
We present a complete Visible Light Communication (VLC) system for experimental Vehicular VLC (V-VLC) research activities. Visible light is becoming an important technology complementing existing Radio Frequency (RF) technologies such as Cellular V2X (C-V2X) and Dedicated Short Range Communication (DSRC). In this scope, first works helped introducing new simulation models to explore V-VLC capabilities, technologies, and algorithms. Yet, experimental prototypes are still in an early phase. We aim bridging this gap with our system, which integrates a custom-made driver hardware, commercial vehicle light modules, and an Open Source signal processing implementation in GNU Radio, which explicitly offers rapid prototyping. Our system supports OFDM with a variety of Modulation and Coding Schemes (MCS) and is compliant to IEEE 802.11; this is in line with the upcoming IEEE 802.11 LC standard as well. In an extensive series of experiments, we assessed the communication performance by looking at realistic inter vehicle distances. Our results clearly show that our system supports even higher order MCS with very low error rates over long distances.

Analyse sicherheitskritischer Software für RISC-V Prozessoren - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (MBMV 2019-22.Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2019))
In diesem Artikel stellen wir eine Methode zur nicht-invasiven dynamischen Speicher- und IO-Analyse mit QEMU für sicherheitskritische eingebettete Software für die RISC-V Befehlssatzarchitektur vor. Die Implementierung basiert auf einer Erweiterung des Tiny Code Generator (TCG) des quelloffenen CPU-Emulators QEMU um die dynamische Identifikation von Zugriffen auf Datenspeicher sowie auf an die CPU angeschlossene IO-Geräte. Wir demonstrieren die Funktionalität der Methode anhand eines Versuchsaufbaus, bei dem eine Schließsystemkontrolle mittels serieller UART-Schnittstelle an einen RISC-V-Prozessor angebunden ist. Dieses Szenario zeigt, dass ein unberechtigter Zugriff auf die UART-Schnittstelle frühzeitig aufgedeckt und ein Angriff auf eine Zugangskontrolle somit endeckt werden kann.

QEMU for Dynamic Memory Analysis of Security Sensitive Software - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph; Driessen, Benedikt (2nd International Workshop on Embedded Software for Industrial IoT in conjunction with DATE 2019)

QEMU Support for RISC-V: Current State and Future Releases - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (2nd International Workshop on RISC-V Research Activities)
It its current Version 3.1.0 QEMU supports RISC-V RV32GC and RV64GC software emulation in user and full system mode. We will first give an overview of the current state of the QEMU RISC-V implementation. Thereafter, we will present the DecodeTree tool, which will be available with the next QEMU release. DecodeTree is a code generator included in QEMU that can generate the program logic for extracting and decoding opcodes and operands from a formal instruction list of the target architecture. This enables the structured implementation of just-in-time compilations to guarantee that the QEMU implementation meets the ISA specification. As such, we completely replaced the existing RISC-V RV32GC and RV64GC implementations by DecodeTree generations in the next official QEMU release, which is expected in spring 2019. We will demonstrate the DecodeTree applications by the example of RISC-V ISA subset configurations.

Alloy Design for Biomedical Applications in Additive Manufacturing - Hoyer, Kay-Peter; Schaper, Mirko (TMS 2019 148th Annual Meeting & Exhibition Supplemental Proceedings)

Surface Inoculation of Aluminium Powders for Additive Manufacturing Guided by Differential Fast Scanning Calorimetry - Tasche, Lennart; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Grundmeier, Guido; Schaper, Mirko; Keßler, Olaf (TMS 2019 148th Annual Meeting & Exhibition Supplemental Proceedings)

Einfluss von Eigenspannungen und Oberflächenrauheit additiv gefertigter Komponenten aus 316L auf die Beschichtbarkeit und Ermüdungsfestigkeit,

Adhesion of HVOF sprayed WC-Co coatings on additively processed 316L

Creating round focused micro-jets from rectangular nozzles - Inguva, Venkatesh; Graceffa, Rita; Schulz, Joachim; Bilsel, Osman; Perot, Blair J. (Journal of Mechanical Science and Technology)

Multi-stage reinforcement learning for object detection - König, Jonas; Malberg, Simon; Martens, Martin; Niehaus, Sebastian; Krohn-Grimberghe, Artus; Ramaswamy, Arunselvan (Science and Information Conference)

On the design of heat exchanger equipment for novel-type isobaric expansion engines - Knoke, Torben; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Applied Thermal Engineering)

Untersuchung des Dosierverhaltens von Carbonfaserrezyklaten für den Einsatz im gleichläufigen Doppel-schneckenextruder - Malatyali, Hatice; Schöppner, Volker (27. Fachtagung Technomer)

Deveploment of thin film sensors: The influence of layer variation on the measurement quality for inline melt temperature measurements - Malatyali, Hatice; Schöppner, Volker; Tillmann, Wolfgang; Kokalj, David (SPE ANTEC)

Vibration welding of components with angled areas in the direction of vibration - Vogtschmidt, Sascha; Schöppner, Volker

Influence of precursor concentration on spray and particle formation in flame spray pyrolysis - Bieber, M.; Tischendorf, R.; Reddemann, M.; Schmid, H.-J.; Kneer, R.
Liquid atomization is expected to be a key process in Flame Spray Pyrolysis, as it determines the primary droplet size and velocity distribution, which represent initial conditions for flame shape and temperature field. A well-defined manipulation of atomization may be achieved by variation of nozzle geometry, injection parameter or fluid properties. However, change of fluid properties, e.g. varying solvents or increasing the precursor concentration, also influences the final particle properties. In this work, the influence of precursor concentration on fluid properties, spray and particle formation in Flame Spray Pyrolysis is experimentally investigated. High-speed shadowgraphy and Phase-Doppler measurements are conducted in a semi-closed combustion chamber with a well-defined burner geometry (SpraySyn burner) that is based on a coaxial atomization principle. By adding precursor to the flammable solvent, resulting spray characteristics, flame shape and appearance are changed in color, shape and mean droplet size distribution. Compared to resulting mean droplet sizes of pure solvent mixtures (D32, 22 μm), mean droplet sizes in the center of the precursor flame at 30 mm above the burner are generally smaller (D32, 18 μm). Persisting high share of small droplets in the droplet size distribution are presented, that presumably origin from an accumulation of metal organic precursor at the droplet surface during combustion, that acts as a diffusive barrier for high volatility solvent and thus reduces droplet evaporation. Sufficiently high above the nozzle exit, increasing the precursor concentration does not affect the radial distribution of mean droplet sizes but leads to increased mean particle sizes. More precursor presumably leads to higher concentrations of prime particles in the flame, thus probability of particle collusion and agglomeration. High-speed imaging at nozzle exit revealed random fluctuations of initial jet diameter, paired with jet axis shifting around 1000 Hz. These superposed fluctuations determine the initial conditions for atomization, induce pulsations in the flame and thus initiate the entire chain of the particle synthesis process.
Keywords: FSP; nanoparticle synthesis; in situ measurements

FVA-Nr. 813 I - Generative Verfahren zur Herstellung von Polymerbauteilen - Menge, Dennis; Walter, Rolf; Schmid, Hans-Joachim; Breuer, Ulf Paul

Optimization of Cooling Utility System with Continuous Self-Learning Performance Models - Peesel, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Dunkelberg, Heiko; Walmsley, Timothy (Energies)
Prerequisite for an efficient cooling energy system is the knowledge and optimal combination of different operating conditions of individual compression and free cooling chillers. The performance of cooling systems depends on their part-load performance and their condensing temperature, which are often not continuously measured. Recorded energy data remain unused, and manufacturers’ data differ from the real performance. For this purpose, manufacturer and real data are combined and continuously adapted to form part-load chiller models. This study applied a predictive optimization algorithm to calculate the optimal operating conditions of multiple chillers. A sprinkler tank offers the opportunity to store cold-water for later utilization. This potential is used to show the load shifting potential of the cooling system by using a variable electricity price as an input variable to the optimization. The set points from the optimization have been continuously adjusted throughout a dynamic simulation. A case study of a plastic processing company evaluates different scenarios against the status quo. Applying an optimal chiller sequencing and charging strategy of a sprinkler tank leads to electrical energy savings of up to 43%. Purchasing electricity on the EPEX SPOT market leads to additional costs savings of up to 17%. The total energy savings highly depend on the weather conditions and the prediction horizon.

System efficient integration of standby control and heat pump storage systems in manufacturing processes - Schlosser, Florian; Seevers, Jan-Peter; Peesel, Ron-Hendrik; Walmsley, Timothy Gordon (Energy)

Design of Robust Total Site Heat Recovery Loops via Monte Carlo Simulation - Schlosser, Florian; Peesel, Ron-Hendrik; Meschede, Henning; Philipp, Matthias; Walmsley, Timothy; Walmsley, Michael; Atkins, Martin (Energies)
For increased total site heat integration, the optimal sizing and robust operation of a heat recovery loop (HRL) are prerequisites for economic efficiency. However, sizing based on one representative time series, not considering the variability of process streams due to their discontinuous operation, often leads to oversizing. The sensitive evaluation of the performance of an HRL by Monte Carlo (MC) simulation requires sufficient historical data and performance models. Stochastic time series are generated by distribution functions of measured data. With these inputs, one can then model and reliably assess the benefits of installing a new HRL. A key element of the HRL is a stratified heat storage tank. Validation tests of a stratified tank (ST) showed sufficient accuracy with acceptable simulation time for the variable layer height (VLH) multi-node (MN) modelling approach. The results of the MC simulation of the HRL system show only minor yield losses in terms of heat recovery rate (HRR) for smaller tanks. In this way, costs due to oversizing equipment can be reduced by better understanding the energy-capital trade-off.

Heat Pump Integration by Pinch Analysis for Industrial Applications: A Review - Schlosser, Florian; Arpagaus, Cordin; Walmsley, Timothy G. (Chemical Engineering Transactions)

Integration of Heat Pump Storage Systems in Manufacturing Systems via Data Farming and Monte Carlo Simulation - Seevers, Jan-Peter; Schlosser, Florian (Chemical Engineering Transactions)

System Efficiency Rating of Industrial Utilities in Electricity Grids with a high share of Variable Renewable Energies - Selleneit, Volker; Stockl, Martin; Philipp, Matthias; Mast, Tanja; Schlosser, Florian (Chemical Engineering Transactions)

InMould-Plasma - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Nordmeyer, T.; Böhnke, Birte; Krampe, Erhard; Asad, Salman (Eröffnung Plasma-Campus bei Plasmatreat GmbH)

Investigation of the bond strength between injection moulded TPU and a reactive, castable polyurethane mass (PU) - Moritzer, Elmar; Jilg, J.; Sibbe, N. (PU MAGAZIN - International)

Investigation of the bond strength between injection moulded TPU and a reactive, castable polyurethane mass (PU) - Moritzer, Elmar; Jilg, J.; Sibbe, N. (TPE Magazine international)

Lebensdauer von Composites und Composite-Metall-Hybridverbindungen - Moritzer, Elmar; Hüttner, Matthias; Krassmann, Dimitri; Wittke, Marius (Werkstoffwoche)

Hochschulbildungsforschung. Theoretische, methodologische und methodische Denkanstöße für die Hochschuldidaktik - Tobias Jenert, Gabi Reinmann, Tobias Schmohl
Keywords: Hochschulbildung; Bildungsforschung; Hochschuldidaktik; Hochschulbildung; Hochschuldidaktik; Forschung; Lehren; Hochschule; Lehre; Lernen

Untangling Faculty Misinformation From an Educational Perspective: Rejoinder to ?The Menace of Misinformation: Faculty Misstatements in Management Education and Their Consequences? - Brahm, T.; Jenert, T. (Journal of Management Education)

Morphology Development in LLDPE Stretch Films Prepared with Different Cast Film Process Parameters - Schöppner, Volker; Bayazian, H.; Yadegari, Ali (77th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

New Analytical Approach to Calculate the Melt Flow within The Co-Rotating Twin Screw Extruder by Using the Performance Mapping Method - Schöppner, Volker; Sporkmann, F.; Heide, Alexander (35th International Conference of the Polymer Processing Society (PPS))

Nieten im Spritzgießprozess zur Verbindung von Hybridbauteilen aus Organoblechen und Metallen - Moritzer, Elmar; Budde, Christopher; Hüttner, Matthias; Krassmann, Dimitri (9. Fügetechnisches Gemeinschaftskolloquium)

Oberflächennachbearbeitung und Kleben von FDM-Bauteilen - Moritzer, Elmar; Hirsch, André (DGM-Seminar für Fortgeschrittene)

Orientation in LLDPE Cast Films Manufactured under Different Processing Parameters - Schöppner, Volker; Bayazian, H.; Yadegari, Ali; Haddad, Hoda (35th PPS)

Plant Design, Stress-Strain Characteristics in Compression and Lifecycle Description of Coiled Filament Mats Based on Production According to Fitzer - Moritzer, Elmar; Westhues, T. (35th PPS)

Plastic droplet welding: bond strength between plastic freeforming structures and continuous fiber-reinforced thermoplastic composites - Moritzer, Elmar; Hirsch, André; Heim, H.-P.; Cherif, C.; Truemper, W. (Welding in the World)

Scale up von Doppelschneckenmaschinen - Schöppner, Volker; Sporkmann, F. (VDI Wissensforum)

Schmelzefilter - Schöppner, Volker; Meilwes, P.; Westhues, K.

Simulation aids compounding success - Schöppner, Volker; Sporkmann, F. (Compounding World)

Simulation der Feststoffförderung im Einschneckenextruder - Schöppner, Volker; Brüning, Florian (WAK Jahresmagazin)

Simulation-based Optimization of Advanced Mixing Elements on Single Screw Extruders - Moritzer, Elmar; Wittke, M. (77th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Spritzgießwerkzeuge mit Heatpipe-Temperierung - Moritzer, Elmar; Kartelmeyer, S.; Hüttemann, B.; Jaroschek, C. (26. Fachtagung über Verarbeitung und Anwendung von Polymeren)

Untersuchung der Verbundhaftung zwischen spritzgegossenen TPUs und einer reaktiven, gießfähigen Polyurethanmasse - Moritzer, Elmar; Jilg, J.; Sibbe, N. (PU MAGAZIN)

Vortrag „Aufschmelzen“ Optimierter Betrieb und Scale-up von Doppelschnecken-Extrudern - Schöppner, Volker; Westhues, K. (VDI Wissensforum)

Zur Wirkung dehnströmungsinduzierender Spritzgießdüsen für glasfaserverstärktes Polypropylen im Sonderverfahren der Spritzgießdirektcompoundierung (SGDC) - Moritzer, Elmar; Jilg, J. (26. Fachtagung über Verarbeitung und Anwendung von Polymeren)

Effect of playing position and time on-court on activity profiles in german elite team handball - Büchel, Daniel; Jakobsmeyer, Rasmus; Döring, Michael; Adams, Michael; Rückert, Ulrich; Baumeister, Jochen (International Journal of Performance Analysis in Sport)

Understanding and Manipulation of Nanoparticle Contact Forces by Capillary Bridges - Schmid, Hans-Joachim; Grundmeier, Guido; Dörmann, Michael; Orive, Alejandro González; de los Arcos, Teresa; Torun, Boray (Particles in Contact)
Since, in the presence of humidity the inter-particle processes are dominated by capillary forces, a fundamental understanding of the water adsorption and the capillary bridge formation is very important. However, the adsorbed water structure and thus the capillary bridge formation is influenced by various parameters like the particle morphology (e.g. particle size, roughness) as well as the surface chemistry (surface energy, adsorbate structure) and therefore needs to be analyzed on a submicroscopic or even molecular basis. A multi-scale approach ranging from experiments on an individual particle level (AFM and liquid bridge simulation) and investigations on small particle ensembles (combined QCM-D/FTIR) up to macroscopic description of bulk behavior is presented in this chapter. In this context, the combined in situ QCM-D/FTIR experiments are bridging the gap between experiments on an individual particle level and macroscopic bulk behavior. Variation of surface chemistry by means of adsorption of functional organic molecules allows for the correlation of macroscopic particle behavior to nanoscopic effects like the presence and structure of adsorbate layers as well as the formation of capillary bridges while keeping the disperse properties constant. Besides extensive experimental work, simulations of capillary bridges formed by condensation from humid air are presented. It is clearly shown that well known approximations which have been introduced for micron-sized particles are not valid any more for nano-scaled particles. The forces between nanoparticles by static liquid bridges and their dependency on particle size, contact angle, humidity and interparticle distance are discussed in detail. Furthermore, capillary forces during separation of particles are studied thoroughly and a constitutive law based on a contact stiffness allows the transfer to DEM simulations of wet powders. Finally, it is demonstrated by comparison to Molecular Dynamics simulations, that the used continuum approach to simulate capillary bridges might even be used down to particle sizes of a few nanometers, if some additional effects are considered correctly.

Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

General framework for the analysis of imperfections in nonlinear systems - Santandrea, Matteo; Stefszky, Michael; Silberhorn, Christine (Optics Letters)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Counter-propagating photon pair generation in a nonlinear waveguide - Luo, Kai-Hong; Ansari, Vahid; Massaro, Marcello; Santandrea, Matteo; Eigner, Christof; Ricken, Raimund; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Quasiprobability distributions for quantum-optical coherence and beyond - Sperling, Jan; Vogel, W (Physica Scripta)

Measuring coherence of quantum measurements - Cimini, Valeria; Gianani, Ilaria; Sbroscia, Marco; Sperling, Jan; Barbieri, Marco (Physical Review Research)

What can single photons do what lasers cannot do? - Rezai, Mohammad; Sperling, Jan; Gerhardt, Ilja (Quantum Science and Technology)

Benchmarking of Gaussian boson sampling using two-point correlators - Phillips, D. S.; Walschaers, M.; Renema, J. J.; Walmsley, I. A.; Treps, N.; Sperling, Jan (Physical Review A)

Photonic quantum walks with four-dimensional coins - Lorz, Lennart; Meyer-Scott, Evan; Nitsche, Thomas; Potoček, Václav; Gábris, Aurél; Barkhofen, Sonja; Jex, Igor; Silberhorn, Christine (Physical Review Research)

Detailed study of Gaussian boson sampling - Kruse, Regina; Hamilton, Craig S.; Sansoni, Linda; Barkhofen, Sonja; Silberhorn, Christine; Jex, Igor (Physical Review A)

Eigenvalue measurement of topologically protected edge states in split-step quantum walks - Nitsche, Thomas; Geib, Tobias; Stahl, Christoph; Lorz, Lennart; Cedzich, Christopher; Barkhofen, Sonja; Werner, Reinhard F; Silberhorn, Christine (New Journal of Physics)

A high dynamic range optical detector for measuring single photons and bright light - Tiedau, Johannes; Meyer-Scott, Evan; Nitsche, Thomas; Barkhofen, Sonja; Bartley, Tim J.; Silberhorn, Christine (Optics Express)

Inklusiver Unterricht aus Sicht von Grundschullehrkräften. Die Bedeutung von persönlichen Ressourcen - Görel, Gamze